Bibliographie zur äthiosemitischen und kuschitischen Sprachwissenschaft VII: 2002 (Aethiopica, 2004)
Bibliography for the Study of Ethiosemitic, Cushitic and Omotic Languages.
Keywords: Bibliography; Linguistics; Ethiosemitic; Cushitic; Omotic